Tingkat Keramahan Lingkungan pada Alat Tangkap Purse Seine di Desa Laha, Ambon - Fuja Kinanti Hatao; Exist Saraswati; M. Tajuddin Noor (Zebra: Jurnal Ilmu Peternakan dan Ilmu Hewani, 2026)
The environmental friendliness of a fishing gear is an important component in sustainable fisheries management. The use of environmentally friendly fishing gear that complies with the Code of Conduct for Responsible Fisheries is absolutely necessary. Environmental friendliness refers to the ability of a fishing gear to catch fish with minimal environmental impact, because even though the fishing gear can catch fish well, the fishing gear can still cause problems with the marine environment, such as damage to coral reefs and non-selective fishing. The purse seine fishing gear used by fishermen in Laha Village, Ambon is one of the effective fishing gears in catching various types of pelagic fish such as scad, tuna, lemuru, skipjack and mackerel. Purse Seine fishing gear also has a negative impact on the marine ecosystem and therefore this study was conducted to determine the environmental friendliness of Purse Seine fishing gear. The research method that will be used is a descriptive method, namely interviews using questionnaires given to fishermen and data collection through field observations. Based on the results of the study, the Purse Seine fishing gear in Laha Village, Ambon is used to catch several types of small and large pelagic fish and the main catch is scad and skipjack tuna. Based on the calculation results of the criteria for environmentally friendly fishing gear, a score of 30 was obtained, so it can be concluded that the Purse Seine fishing gear in Laha Village, Ambon is included in the very environmentally friendly category. It is recommended that fishermen in Laha Village prioritize their safety and security during the fishing process and while sailing.